Outlook for the grain market - Nick Butler (Intereconomics, 1984)
With all the indications suggesting that the current imbalance between supply of and demand for grain will continue for the foreseeable future, and with a steady surplus both keeping prices down and forcing on governments measures to reduce output and stocks, attention is turning to South East Asia, a region which, due to the rapid growth of both its population and per capita income, seems to offer the best prospects of medium and long-term increases in demand. How realistic are the hopes that South East Asia will be able to absorb a substantial part of the world's grain surplus?
Keywords: 330; South East Asia